Interaction between intrinsically disordered regions in transcription factors Sp1 and TAF4. (24th August 2016) - Hibino, Emi; Inoue, Rintaro; Sugiyama, Masaaki; Kuwahara, Jun; Matsuzaki, Katsumi; Hoshino, Masaru
Abstract: The expression of eukaryotic genes is precisely controlled by specific interactions between general transcription initiation factors and gene‐specific transcriptional activators. The general transcription factor TFIID, which plays an essential role in mediating transcriptional activation, is a multisubunit complex comprising the TATA box‐binding protein (TBP) and multiple TBP‐associated factors (TAFs). On the other hand, biochemical and genetic approaches have shown that the promoter‐specific transcriptional activator Sp1 has the ability to interact with one of the components of TFIID, the TBP‐associated factor TAF4. We herein report the structural details of the glutamine‐rich domains (Q‐domains) of Sp1 and TAF4 using circular dichroism (CD) and heteronuclear magnetic resonance (NMR) spectroscopy. We found that the two Q‐domains of Sp1 and four Q‐domains of TAF4 were disordered under physiological conditions. We also quantitatively analyzed the interaction between the Q‐domains of Sp1 and TAF4 by NMR and surface plasmon resonance, and detected a weak but specific association between them. Nevertheless, a detailed analysis of CD spectra suggested that any significant conformational change did not occur concomitantly with this association, at least at the level of the overall secondary structure. These results may represent a prominent and exceptional binding mode for the IDPs, which are not categorized in a well‐accepted concept of "coupled folding and binding."